DUNIA MMO GAME PARA GAMER DI KOMUNITAS FORUM INDOGAMERS - Wawan Wartono (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
The number of gamers has increased rapidly during the Covid-19 pandemic. However, researchers in this regard tend to look at negative aspects such as addiction and mental health. It is very rare for research related to MMO Games or Online Games that examines and interprets games from the point of view of the experience and articulation of the gamers themselves. Researchers are trying to take a more neutral perspective or a middle ground in viewing this online game phenomenon through the research